Investigating the role of trade unions in pension fund investment: a case of trade unions in South Africa - Fumpa, Humphrey (My University, 2011)
South African pension fund assets are estimated at ZAR 1 924 billion. This is a large pool of funds that is collected from workers. However, the contention is that workers, whose savings make up the assets of pension funds have little influence on how these funds are used. As a result, most of the funds are invested in corporations, which do not reflect the aspirations of the labour movement. The argument is that if these funds were under the control and direction of the working class, enormous contributions would be made towards economic growth, socially useful investments, community development, employment creation and growth in retirement benefits. The purpose of this study was to assess the extent to which trade unions have been able to promote the interest of members and direct pension fund investment in sectors that will have a positive impact on working families and their communities in South Africa. This study adopted a qualitative method, using purposive sampling and a semi-structured outline to conduct face-to-face interviews with union unions and fund managers. Collected data were analyzed using content analysis. Results were categorized into two distinct parts. The first part looked at pension fund investment regulation and management, asset allocation, investment practices and composition of the pension board. The second part described trade unions’ role in promoting the interest of pension fund members; the extent of their influence in pension fund investments; their contribution to strengthening pension fund governance and how to enhance their influence and control of pension fund investments. The study suggests that trade unions have a critical role to play in pension fund management through their representation on the pension boards. However, the success can only be achieved if trade unions have a clear policy that spells out labour’s agenda on pension issues. Additionally, union trustees should be supported to getting involved in understanding their plans and develop capacities in capital market strategies, investment and economic development.
MA (Labour Policies and Globalisation), Faculty of Humanities, University of the Witwatersrand, 2011
Keywords: trade unions; pension fund investments